2020
DOI: 10.1007/s12144-020-01158-5
|View full text |Cite
|
Sign up to set email alerts
|

The Metacognitive Training for obsessive-compulsive disorder: A pilot study

Abstract: More than 50% of patients with obsessive-compulsive disorder (OCD) do not receive first-line psychological treatment such as cognitive-behavioral therapy with exposure and response prevention. To narrow this treatment gap, there is an urgent need for therapies that are easy to disseminate and highly accepted by patients. The aim of the present pilot study was to evaluate the effectiveness of the Metacognitive Group Training for OCD (MCT-OCD). Fifty patients with OCD participated in the MCT-OCD for 4 weeks duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 65 publications
(71 reference statements)
0
12
0
Order By: Relevance
“…Besides showing promising in-session as well as between-session effects, the MCT-OCD in its pilot version has also been shown to be highly accepted by patients with OCD [48], to have module-specific positive effects [50], and to result in a reduction of OC symptoms with large effect sizes [49]. As OCD patients often do not receive the most effective treatment for OCD (CBT with ERP), the MCT-OCD aims to provide a treatment option that is low threshold and highly accepted by patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides showing promising in-session as well as between-session effects, the MCT-OCD in its pilot version has also been shown to be highly accepted by patients with OCD [48], to have module-specific positive effects [50], and to result in a reduction of OC symptoms with large effect sizes [49]. As OCD patients often do not receive the most effective treatment for OCD (CBT with ERP), the MCT-OCD aims to provide a treatment option that is low threshold and highly accepted by patients.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that the MCT-OCD modules specifically reduce the biases that are addressed in each module. Evaluation of the effectiveness of the MCT-OCD pilot study demonstrated that patients' OC symptoms decreased with a large effect from baseline to post assessment (η 2 partial = 0.50) [49]. However, the pilot study lacked a control group and included only patients currently undergoing a comprehensive inpatient treatment, limiting the conclusions.…”
Section: Metacognitive Training For Patients With Ocdmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in one study, the effectiveness of MCT was reduced in patients with moderate to severe delusional symptoms, which underscores the need for a specific adaptation of metacognitive training for the acute setting (van Oosterhout et al, 2014). MCT has also been adapted to several other psychiatric disorders such as depression (D-MCT; Jelinek et al, 2015), depression in later life (MCT-Silver; Schneider et al, 2018), obsessive-compulsive disorder (Miegel et al, 2020), bipolar disorder (Haffner et al, 2017), borderline personality disorder (Schilling et al, 2015) and problem gambling (Gehlenborg et al, 2020). In addition, it is now available as a mobile application (Lüdtke et al, 2018).…”
Section: From Mct To Mct-acutementioning
confidence: 99%
“…Metacognitive Training-Silver (MCT-Silver; www.uke.de/ mct-silver) is a low-threshold, CBT-based group intervention developed for older adults with depression. It is based on Metacognitive Training for psychosis (MCT; Moritz et al, 2014), which inspired the development of further MCTs for depression among young and middle-aged adults (D-MCT; Jelinek et al, 2015Jelinek et al, , 2016Jelinek et al, , 2019, obsessive-compulsive disorder (Miegel et al, 2021), borderline personality disorder (Schilling et al, 2018), pathological gambling (Gehlenborg et al, 2021), and bipolar disorder (Haffner et al, 2018). Several other metacognition-based interventions have been developed over the past years in addition to MCT (for a review see Moritz et al, 2018).…”
Section: Introductionmentioning
confidence: 99%